1977
DOI: 10.1002/j.1879-3479.1977.tb00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Medroxyprogesterone Acetate (Depo‐Provera®) as an Injectable Contraceptive

Abstract: Depo-Provera injections appear to be a safe and effective alternative for women who cannot tolerate the estrogenic side effects associated with oral contraceptives or the pain and bleeding associated with IUDs. However, women considering the method should be fully aware of the possible risks: (a) inability to withdraw the drug promptly in the event of a serious reaction, (b) disruption of menstrual patterns, and (c) delayed return of fertility after discontinuing therapy. Some women may consider the required t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Compared to past use of other contraceptive methods, past IUD use does not impair a woman's ability to become pregnant [7,19,23,27]. Most of these cohort studies evaluated women who had their IUDs removed electively to become pregnant.…”
Section: Commentmentioning
confidence: 98%
See 1 more Smart Citation
“…Compared to past use of other contraceptive methods, past IUD use does not impair a woman's ability to become pregnant [7,19,23,27]. Most of these cohort studies evaluated women who had their IUDs removed electively to become pregnant.…”
Section: Commentmentioning
confidence: 98%
“…It has been suggested [4] that the reason for the higher risk of PID in IUD users is that IUDs do not protect against PID while the use of other contraceptive methods provides some protection. As a consequence of the apparent association between IUD use and PID and the higher risk of infertility following PID [5], some physicians are reluctant to provide IUDs for women who may wish to have children.Studies evaluating conception rates for women who had their IUDs removed to become pregnant have shown that IUD use did not impair their fertility [6][7][8][9][10][11][12][13][14][15]. The primary limitation of these studies is that they only evaluated pregnancy outcomes or infertility rates for women who discontinued IUD use for reasons other than pregnancy or planned pregnancy.…”
mentioning
confidence: 99%
“…In the United States, the drug has not as yet been approved by the FDA. The method is highly effective (Ellinas, 1977). Unsatisfactory aspects are breakthrough bleeding and the required visit to the doctor every 3 months.…”
Section: Injectable Progestagensmentioning
confidence: 99%
“…Estrogens have usually been considered the culprit. Most authors think that progesterone, on the other hand, does not raise BP (2,4,11,13,14,17,18) and so may be used as a contraceptive agent without fear of causing hypertension. Leiman (9), however, reported significant BP changes in 24% of 1050 patients treated with medroxyprogesterone acetate (MPA) (Depo-Provera, The Upjohn Company, Kalamazoo, MI, USA) as defined by increases or decreases in systolic (20 mm Hg) and/or diastolic (10 mm Hg) BP.…”
Section: Introductionmentioning
confidence: 99%